Telaah Kritis Film Indie Jember: Studi Distribusi Produk Kreatif Berbasis Digital - Kemas Aditya (Fakultas Ilmu Budaya, 2025)
This study highlights the evolution of indie film marketing strategies in Jember, which now rely more on digital marketing than traditional promotional methods. By utilizing an Integrated Marketing Communications (IMC) approach, the research explores how digital marketing, particularly through social media and local influencers, successfully aids indie films in reaching a broader audience. IMC, as an integrated approach, combines various communication channels, such as digital advertising, public relations, and social media, to ensure a consistent and impactful message. In this study, the IMC approach is applied to maximize the effectiveness of digital marketing in Jember. A SWOT analysis method is used to examine the strengths, weaknesses, opportunities, and threats in applying digital marketing for indie films. The findings show that a digital marketing strategy through IMC effectively increases audience numbers, especially through platforms like Instagram and YouTube, which enable direct interaction between filmmakers and audiences. However, challenges such as digital content competition and dependency on platform algorithms still affect marketing reach. These findings are expected to provide local filmmakers with insights into optimizing film marketing through an integrated IMC approach, while also addressing budget and resource limitations in indie film production environments.
Reupload file repositori 30 januari 2026_Kurnadi/Mita
Keywords: Digital Marketing; Indie Film